Skin cancer in organ transplant recipients - Imko-Walczuk, Beata; Ankudowicz, Anna; Jaśkiewicz, Janusz; Lizakowski, Sławomir; Dębska-Ślizień, Alicja; Rutkowski, Bolesław (Dermatology Review/Przegląd Dermatologiczny, 2011)
Cancer is one of the main causes of death after successful organ transplantation. The constantly rising number of patients living with transplanted organs, but at the same time higher morbidity rate, aggressive, rapid development of malignant tumours and unfavourable prognosis, require a special oncological approach in this population. In the group of patients with transplanted organs, skin cancers are the most common malignancies and present an atypical clinical picture different than in the group of immunocompetent patients. In the discussed population skin cancers – squamous cell carcinoma as well as basal cell carcinoma – are the most common types of tumours. Kaposi’s sarcoma, melanoma, lymphoma, anogenital cancer, Merkel cell cancer and other rare tumours may occur more often in patients receiving immunosuppressive therapy. It is essential to become familiar with the features and clinical distinctness of these malignancies in patients with transplanted organs, in order to recognize them in the very early stage of neoplastic process.